2008
DOI: 10.1016/j.pharmthera.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanisms of viral induced asthma: New therapeutic directions

Abstract: Asthma is a common and debilitating disease that has substantially increased in prevalence in Western Societies in the last 2 decades. Respiratory tract infections by respiratory syncytial virus (RSV) and rhinovirus (RV) are widely implicated as common causes of the induction and exacerbation of asthma. These infections in early life are associated with the induction of wheeze that may progress to the development of asthma. Infections may also promote airway inflammation and enhance T helper type 2 lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
117
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 414 publications
(489 reference statements)
1
117
0
1
Order By: Relevance
“…Recent reports demonstrated that extracellular delivery of oligonucleotides is efficiently transported toward lysosomal TLR through the mobilization of scavenger receptors (42,43). Moreover, our model mimics the clinical situation associated with virus-induced asthma exacerbation, including an increase of AHR, eosinophilic airway inflammation, innate immune cell infiltrate, allergen-specific Ig levels, development of Th2 cells, and secretion of Th2-associated chemokines (6,21,44). Finally, in mice treated with dsRNA/OVA as well as in animals during respiratory viral infection and during respiratory syncitial virus-enhanced allergic inflammation (45,46), CD8 + T cells represent the majority of T lymphocytes infiltrating lung tissue and draining LNs (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Recent reports demonstrated that extracellular delivery of oligonucleotides is efficiently transported toward lysosomal TLR through the mobilization of scavenger receptors (42,43). Moreover, our model mimics the clinical situation associated with virus-induced asthma exacerbation, including an increase of AHR, eosinophilic airway inflammation, innate immune cell infiltrate, allergen-specific Ig levels, development of Th2 cells, and secretion of Th2-associated chemokines (6,21,44). Finally, in mice treated with dsRNA/OVA as well as in animals during respiratory viral infection and during respiratory syncitial virus-enhanced allergic inflammation (45,46), CD8 + T cells represent the majority of T lymphocytes infiltrating lung tissue and draining LNs (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Allergens and respiratory viruses act synergistically in the expression of asthma symptoms in adults and children [13,33]. RV-induced epithelial cytotoxicity could increase the penetration and effects of allergens, leading to further induction of inflammation [87,88]. Synergy between virus and mite (Dermatophagoides pteronyssinus antigen 1)-induced inflammation may also occur through combined nuclear factor-kB activation [89].…”
Section: Mechanisms Of Virus-induced Exacerbationmentioning
confidence: 99%
“…It is a complex disease characterized by airway hyper-responsiveness, inflammation, and tissue remodeling resulting in episodic airflow obstruction and clinical symptoms of wheezing, coughing, and shortness of breath (2). Asthma is a major public health issue in the United States as it is the number one illness leading to school absences in children (3), and in 2010 alone asthma accounted for 3404 deaths and 1.8 million emergency department visits (4).…”
mentioning
confidence: 99%